PENGGARUH KENAIKAN HARGA MINYAK GORENG TERHADAP PENDAPATAN PENJUAL GORENGAN KAKI LIMA - Ahmad Afshohuddin; Maulana Yusuf; Awal Habibah (CV. Aksara Global Akademia, 2024)
This research aims to determine the effect of cooking oil prices on the income of sellers in the Mayang Mangurai Village, Jambi City. The method used in this research is a quantitative method with data collection through observation, questionnaires, interviews and documentation. The types of data used in this study are secondary and primary data. The number of samples in this study were 39 fried food sellers in the Mayang Mangurai Village, Jambi City. Data analysis using simple linear regression. From the research results obtained the regression equation as follows. Y = 37,457 – 0,877X means that the oil price variable has a positive and significant effect on the seller's income variable. This was also tested using the t test which can be seen from the t count 8,539 > t table 2.026 and a significance of 0.000 <0.05, which means that oil price X has a significant influence on the income of seller Y in the Mayang Mangurai Village, Jambi City. For the R2 determination test, the data processing results showed that the R2 value was 0,663, which means that the influence of the oil price variable and the seller's income variable was 63,3% and the remaining 37,7% was influenced by other factors not included in this study.